Evaluating the technical activities of vocational education schools in the city of Baghdad (Journal of the College of Basic Education, 2023)
Education is one of the means concerned with preparing and developing the personality of the individual in all respects, and that education is subject to development through the scientific and technical progress taking place in the world, which consequently affects education and the realization of its aspirations for the future. Art education is considered one of the parts of education and confirms and helps to achieve the aspirations of education, as it develops the personality of the learner in terms of scientific, skill and emotional aspects, by linking education with art, as the philosophy of art education is education through art, so art is considered part of the educational process and a means of Expression and achievement of the goals of education in general and art education in particular, "as art is a means that conveys through the way the thoughts and feelings of the artist to the recipient so that he can feel this experience that without the artist he would not have been able to feel it."